Solvent-free encapsulation of curing agents for high performing one-component epoxy adhesives. (1st December 2020) - Jee, Sung Min; Ahn, Cheol-Hee; Park, Jong Hyuk; Kim, Tae Ann; Park, Min
Abstract: One-component epoxy adhesives, in which the epoxy resin and curing agent are premixed, have many commercial advantages including reduced working time and stable performance. However, these adhesives suffer from a short shelf life even at room temperature. Here, core-shell structured curing agents were prepared via a dry particle coating (DPC) process that improved the storage stability of one-component epoxy adhesives. The DPC process is a simple, economic, and solvent-free method to fabricate core-shell structured materials using mechanical forces. Graphene nanoplatelets (GNPs) were used as encapsulating materials due to their high thermal conductivity and large surface areas. With the GNP-encapsulated curing agents, a one-component epoxy adhesive displayed significantly enhanced storage stability while maintaining its fast curing behavior. In particular, the pot life of the adhesive increased to 60 days, which is over two-times longer than that of a pristine epoxy adhesive. The curing temperature increased by up to 5.6 °C, which is a smaller increase than that observed when non-thermally conductive materials were used for encapsulation. Furthermore, the GNPs provided reinforcement in the cured epoxy adhesive, thereby improving the lap shear strength by 20–30%. Highlights: A core-shell latent curing agent was prepared via a dry particle coating process. The dry particle coating process is a simple, solvent-free, and economic method. GNP shell layers enhanced storage stability while kept the fast curing kinetics. Lap shear strength was enhanced due to better dispersion of the GNPs in epoxy resin.